Transforming a Face-to-Face Legacy Intervention to a Web-Based Legacy Intervention for Children With Advanced Cancer. Issue 1 (February 2020) - Akard, Terrah Foster; Wray, Sarah; Friedman, Debra L.; Dietrich, Mary S.; Hendricks-Ferguson, Verna; Given, Barbara; Gerhardt, Cynthia A.; Hinds, Pamela S.; Gilmer, Mary Jo
Abstract : Research is needed to examine new and innovative web-based intervention delivery methods that are feasible, cost-effective, and acceptable to children and their families to increase access to palliative care services in the home and community. Our previous work included the development of a legacy intervention using face-to-face digital storytelling for children with cancer that showed feasibility and strong promise to improve child outcomes. However, face-to-face intervention delivery techniques limited our recruitment, thus decreasing sample size and potential access to broader populations. Here we present the systematic steps of the development of a web-based legacy intervention for children (7-17 years of age) with relapsed or refractory cancer and their parent caregivers. Counts and frequencies for parent (n = 81) reports on satisfaction surveys are presented and parent suggestions for future work. Results suggest the web-based legacy intervention is feasible and acceptable, with parent-perceived beneficial outcomes for the child, parent, and family. Results provide a foundation for web-based intervention development in palliative care and the implementation of a theoretically grounded intervention to reduce suffering of seriously ill children and their family members, thereby advancing the science of symptom management in vulnerable palliative care populations.